Physics Examples
F=maF=ma
FF | == | 6N6N |
mm | == | ?? |
aa | == | 3ms23ms2 |
Step 1
Step 1.1
Rewrite the equation as ma=Fma=F.
ma=Fma=F
Step 1.2
Divide each term in ma=Fma=F by aa and simplify.
Step 1.2.1
Divide each term in ma=Fma=F by aa.
maa=Famaa=Fa
Step 1.2.2
Simplify the left side.
Step 1.2.2.1
Cancel the common factor of aa.
Step 1.2.2.1.1
Cancel the common factor.
maa=Fa
Step 1.2.2.1.2
Divide m by 1.
m=Fa
m=Fa
m=Fa
m=Fa
m=Fa
Step 2
Step 2.1
Substitute 6N for F.
m=6Na
Step 2.2
Substitute 3ms2 for a.
m=6N3ms2
m=6.00N3.00ms2
Step 3
Step 3.1
Cancel the common factor of 6.00 and 3.00.
Step 3.1.1
Factor 3.00 out of 6.00N.
m=3.00(2N)3.00ms2
Step 3.1.2
Cancel the common factors.
Step 3.1.2.1
Factor 3.00 out of 3.00ms2.
m=3.00(2N)3.00(1ms2)
Step 3.1.2.2
Cancel the common factor.
m=3.00(2N)3.00(1ms2)
Step 3.1.2.3
Rewrite the expression.
m=2N1ms2
m=2N1ms2
m=2N1ms2
Step 3.2
Rewrite N as kgms2.
m=2(kgms2)1ms2
Step 3.3
Cancel ms2.
Step 3.3.1
Cancel ms2.
m=2(kgms2)1ms2
Step 3.3.2
Divide 2(kg) by 1.
m=2(kg)
m=2kg
m=2kg
Step 4
Round to 3 significant figures.
m=2.00kg